5S Study: Safe and Simple Single Shot Pulmonary Vein Isolation With Pulsed Field Ablation Using Sedation. (26th May 2022) - Schmidt, Boris; Bordignon, Stefano; Tohoku, Shota; Chen, Shaojie; Bologna, Fabrizio; Urbanek, Lukas; Pansera, Francesco; Ernst, Matthias; Chun, K.R. Julian
Abstract : Background: Pulsed field ablation represents an energy source specific for ablation of cardiac arrhythmias including atrial fibrillation. The aim of the study was to describe the adoption and the process of streamlining procedures with a new ablation technology. Methods: All-comer atrial fibrillation patients (n=191; mean age 69±12 years) underwent catheter ablation with a pulsed field ablation ablation device exclusively using analog-sedation. In the validation phase (n=25), device electrogram quality was compared with a circular mapping catheter to assess pulmonary vein isolation and esophageal temperature monitoring was used. In the streamline phase (n=166), a single-catheter approach was implemented. Postprocedural cerebral magnetic resonance imaging was performed in 53 patients. In 52 patients, esophageal endoscopy was performed at day 1 after the procedure. Follow-up was performed using 72 hours Holter ECGs. Results: On a pulmonary vein basis, pulmonary vein isolation rate was 100% including a single shot isolation rate of 99.5%. The electrogram information of the pulsed field ablation catheter and the circular mapping catheter were 100% congruent. Neither esophageal temperature rises nor esophageal thermal injury were observed. Two minor strokes occurred, presumable due to air embolism during catheter exchanges through the large bore sheath (13.8 F ID). In the streamline phase, reduced procedure times (46±14 versus 38±13 minutes, P =0.004), no further strokes and a low incidence of silent cerebral injury (10/53 patients; 19%) were noted. During short-term follow-up, 17/191 patients (9%) had a atrial tachyarrhythmia recurrence. Conclusions: The pulsed field ablation device allows for simple and safe simple single shot pulmonary vein isolation using standard sedation protocols. Procedural speed and efficacy are remarkable and streamlining measures have added safety.